Commentary: Technology Talk With a Grade Two Student (LEARNing Landscapes, 2013)
In this interview, elementary grade level student Samuel Bradshaw-Truesdale discusses how he uses technology—ranging from Smart tables and Smart boards to computers and the Internet—both at home and in the classroom. He talks about how technology helps him solve word and mathematic problems as well as build LEGO robots.
Keywords: interview; technology; elementary; classroom; home